Ugi post-condensation copper-triggered oxidative cascade towards pyrazoles - Santos, Aurélie Dos; El Kaim, Laurent; Grimaud, Laurence; Ronsseray, Caroline (Beilstein Journal of Organic Chemistry, 2011)
Pyrazolidinones were prepared in a two-step sequence starting from α-hydrazonocarboxylic acids. After a four-component Ugi coupling, the resulting hydrazone was engaged in a copper triggered [3 + 2] cycloaddition/aerobic oxidation cascade.
Keywords: aerobic oxidation; copper(II); [3 + 2] cycloaddition; hydrazone; isocyanide; pyrazolidinone